2009
DOI: 10.3113/fai-2009-0398
|View full text |Cite
|
Sign up to set email alerts
|

Calcaneal Lengthening for Planovalgus Deformity in Children with Cerebral Palsy

Abstract: In ambulatory children with cerebral palsy calcaneal lengthening is an effective procedure for the correction of mild to moderate planovalgus foot deformities. In nonambulatory children with severe plano-valgus deformities of the foot, calcaneal lengthening cannot be recommended because of the high relapse rate in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…Third, each patient was immobilized in a short-leg cast and remained nonweightbearing for 5 to 6 weeks after surgery. Previous studies have reported on various cast durations, ranging from 4 to 8 weeks [1,9,10,16,21,33,37]. However, in these previous studies, graft failure did not seem to be associated with cast duration.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Third, each patient was immobilized in a short-leg cast and remained nonweightbearing for 5 to 6 weeks after surgery. Previous studies have reported on various cast durations, ranging from 4 to 8 weeks [1,9,10,16,21,33,37]. However, in these previous studies, graft failure did not seem to be associated with cast duration.…”
Section: Discussionmentioning
confidence: 89%
“…As a result, younger patients maintained greater correction than did older patients with planovalgus deformity. Although previous studies have reported the severity of initial deformity [33] and ambulatory status [9,23,38] as factor affecting extent of correction, the effects of age on the extent of correction have not been well documented. We speculate that the more rigid the feet are, the lower the extent of correction achieved by calcaneal lengthening will be; and, because older patients may be more rigid, older age may hence result in a reduced extent of correction after the surgery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most of these feet also present when the deformity is not very severe because they become symptomatic earlier due to high force demands of the foot. Ambulatory children have had significantly better clinical and radiological outcomes (according to Mosca's criteria) than nonambulating children with calcaneal lengthening for correction of mild-to-moderate planovalgus deformity [10]. Calcaneal lengthening with concomitant peroneus brevislengthening is an effective procedure for correcting a planovalgus foot deformity; however, it should be noted that, for patients with a 23°AP talus-first metatarsal angle, 36°lateral talus-first metatarsal angle, and 72 % naviculocuboid overlap, additional procedures should also be considered [11].…”
Section: Varus Feetmentioning
confidence: 99%
“…Subsequently, numerous studies have reported the success of calcaneal lengthening for treatment of symptomatic flatfoot deformity in patients with CP [1, 2, 5, 9, 18-20, 22, 28, 29]. Some authors reported a 25% recurrence rate after calcaneal lengthening and other major limitations to this procedure in patients with CP [2,9]. Additional procedures such as a medial soft tissue procedure, medial bony procedure, or triple arthrodesis could be performed concomitantly with calcaneal lengthening, which depends on severity of the deformity.…”
Section: Introductionmentioning
confidence: 99%